2022
DOI: 10.1097/bpo.0000000000002213
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Pediatric Scoliosis: The Impact of Race and Insurance Type on Access to Nonoperative Treatment for Adolescent Idiopathic Scoliosis

Abstract: Background: Adolescent idiopathic scoliosis (AIS) has evidencebased, nonoperative treatments proven to be effective with early diagnosis and prompt treatment. The purpose of this study was to identify potential disparities in access to nonoperative treatment for AIS. Specifically, we sought to determine the interaction of socioeconomic factors on a major curve magnitude and recommend treatment at the initial presentation. Methods: A retrospective review of AIS patients who underwent surgery at a single tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In the United States, Medicaid insurance is often a proxy for racial and ethnic disparities in health care, which are not just limited to surgical interventions. Recently Heffernan et al 3 reviewed access to nonoperative scoliosis care in patients with AIS compared by insurance status and race/ethnicity. They found that at first presentation to their clinic for scoliosis, AIS patients with public insurance were more likely to have curves that were too big to treat in a brace and were more likely to be Black.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, Medicaid insurance is often a proxy for racial and ethnic disparities in health care, which are not just limited to surgical interventions. Recently Heffernan et al 3 reviewed access to nonoperative scoliosis care in patients with AIS compared by insurance status and race/ethnicity. They found that at first presentation to their clinic for scoliosis, AIS patients with public insurance were more likely to have curves that were too big to treat in a brace and were more likely to be Black.…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade later, Nguyen et al 2 implemented a similar telephone call strategy and were able to successfully to schedule a fracture clinic visit for a hypothetical Medicaid-insured child in <40% of clinics compared with a success rate exceeding 80% if that hypothetical child were privately insured. Another study by Heffernan et al 3 observed that children with adolescent idiopathic scoliosis (AIS) insured by public insurances (like Medicaid) present with larger curves and are more likely to be recommended surgical intervention at the initial first presentation. However; no studies have investigated whether Medicaid-insured patients with AIS experience higher postoperative complications or revisions.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] There is increasing interest regarding the effect of health care disparities on the accessibility and delivery of pediatric orthopaedic care in the United States. [1][2][3][8][9][10][11][12] It is known that children with publicly funded insurance wait longer to access general pediatric orthopaedic care, including scoliosis care. [13][14][15] A recent significant emphasis on understanding the root causes of such disparities as they pertain to adolescent idiopathic scoliosis (AIS) care exists.…”
mentioning
confidence: 99%
“…2,8,12,13,17 At-risk patients in disadvantaged inner-city neighborhoods where in-school screenings are not statemandated are potentially vulnerable to poorer nonoperative scoliosis health care access as they may experience delayed initial referral and missed nonoperative treatments. 12,21 In states where in-school scoliosis screenings are mandated, such as Massachusetts and Texas, SES factors and public versus private insurance have failed to exhibit a clinically meaningful difference in major coronal curve severity at initial orthopaedic presentation. 2,17 However, Heffernan et al 12 recently demonstrated patients with public insurance, lower SES by Area Deprivation Index (ADI), and African American race were at greatest risk of presenting with curve magnitudes outside of acceptable bracing parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation